Self-Taught Classifier of Gateways for Hybrid SLAM - Nguyen, Xuan-Dao; Jeong, Mun-Ho; You, Bum-Jae; Oh, Sang-Rok (IEICE-INST ELECTRONICS INFORMATION COMMUNICATIONS ENG, 2010)
This paper proposes a self-taught classifier of gateways for hybrid SLAM. Gateways are detected and recognized by the self-taught classifier, which is a SVM classifier and self-taught in that its training samples are produced and labeled without user's intervention. Since the detection of gateways at the topological boundaries of an acquired metric map reduces computational complexity in partitioning the metric map into submaps as compared with previous hybrid SLAM approaches using spectral clustering methods, from O(2(n)) to O(n), where n is the number of submaps. This makes possible real time hybrid SLAM even for large-scale metric maps. We have confirmed that the self-taught classifier provides satisfactory consistency and computationally efficiency in hybrid SLAM through different experiments.
Keywords: SIMULTANEOUS LOCALIZATION; ENVIRONMENTS